2011
DOI: 10.1089/ars.2010.3542
|View full text |Cite
|
Sign up to set email alerts
|

Occludin Protein Family: Oxidative Stress and Reducing Conditions

Abstract: The occludin-like proteins belong to a family of tetraspan transmembrane proteins carrying a marvel domain. The intrinsic function of the occludin family is not yet clear. Occludin is a unique marker of any tight junction and is found in polarized endothelial and epithelial tissue barriers, at least in the adult vertebrate organism. Occludin is able to oligomerize and to form tight junction strands by homologous and heterologous interactions, but has no direct tightening function. Its oligomerization is affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 222 publications
5
97
0
1
Order By: Relevance
“…Due to the homology of the marvel domain of the TAMPs and the great variation in the length of their cytosolic tails a heterophilic interaction between the transmembrane domains of all three members has been assumed (Blasig et al, 2011;Westphal et al, 2010). As a matter of fact, Md3 is interacting with both Occl and Tric, at bicellular cell-cell contacts within one plasma membrane (cis-interaction).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the homology of the marvel domain of the TAMPs and the great variation in the length of their cytosolic tails a heterophilic interaction between the transmembrane domains of all three members has been assumed (Blasig et al, 2011;Westphal et al, 2010). As a matter of fact, Md3 is interacting with both Occl and Tric, at bicellular cell-cell contacts within one plasma membrane (cis-interaction).…”
Section: Discussionmentioning
confidence: 99%
“…However, interactions between the homologous marvel domains is unlikely as Occl and Tric are unable to associate heterophilically in the cell contact. Occl and Tric share a homologous coiled-coil and ELL-domain, respectively, which is absent in Md3 (Blasig et al, 2011). Md3 has only an extended N-terminal tail and nearly no C-terminal tail in the cytosol as an intracellular interaction site for cytosolic cisbinding domains of Occl and Tric.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occludin is specifically localized to the TJ at endothelial cell margins (18,21) and links with the cytoskeleton through interactions with accessory proteins [i.e., zonulae occluden (ZO)-1, -2, and -3; Refs. 4,10]. It was previously suggested that while occludin is localized to the TJ, it is not essential for TJ assembly and has no direct "tightening" function (4).…”
mentioning
confidence: 99%
“…The investigated cell junctions, except for ZO-1, are transmembrane proteins with two extracellular loops that are accessible to nucleophilic attacks. Therefore, hydrogen peroxide could oxidize redox sensitive cell junctions directly or may influence different redox sensitive signal transduction pathways that modify the expression and localization of cell junctions [329]. Subsequently, the damaged cell junction proteins may be internalized and degraded within the host cell as shown before for VE-cadherin particularly [330,331].…”
Section: Alteration Of Cell Junction Proteins In Pneumococciinfected mentioning
confidence: 98%